Characterization of the Grafted Bentonite Supports by Gas Chromatography - Ramadan, A.A.; Antakli, S.; Alhaj Sakur, A. (Asian Journal of Chemistry, 2010)
Gas chromatographic analysis technique was used for characterization of the gas chromatographic supports, which prepared from siliceous or natural origin. We studied the bentonite to be used as gas chromatographic support, which consists of aluminosilicate oxides mixture with some other metallic oxides. It possesses a porous structure, which permits its use in gas chromatography. The bentonite was thermally treated at 650ºC to obtain firm granules, and acid washed by 6N-HCl to remove the soluble metallic oxides especially iron oxide, till white granules with mesh range 100-120, were obtained. The specific surface area of the support was measured to be 5.4 m2/g. The superficial structure of the grafted bentonite by silicone SE-52 and dimethylchlorosilane was studied by "inverse gas chromatographic method" using dichloromethane as auxiliary solute plotting log Vs = f( 1/T). We carried out many separations for different mixtures as cyclic and aromatic compounds and normal hydrocarbons. The grafted bentonite supports permit to obtain analytical results characterized with complete and good resolution with high efficiency and reproducibility for all studied columns packed with silicone SE-52 and dimethylchlorosilane grafted bentonite, compared with packed columns with bare bentonite.